2017
DOI: 10.1161/circoutcomes.117.004094
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Management of Cardiovascular Disease in Rural South Africa

Abstract: Background Optimal secondary prevention is critical for the reduction of repeated cardiovascular events and the control of cardiovascular risk factors in this context is essential. Data on secondary prevention of cardiovascular disease (CVD) in sub-Saharan Africa are needed to inform intervention strategies, with a particular focus on local disparities. The aim of this study was to assess CVD management in a rural community in northeast South Africa. Methods and Results We recruited adults aged ≥ 40 years re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Using standardized measurement methods, such as Rapid Estimate of Adult Literacy in Medicine (REALM)[ 39 ] or even some measure of formal education could be more informative. Nevertheless, the use of self-reported illiteracy in large epidemiological studies has been reported in the literature with consistent results [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 77%
“…Using standardized measurement methods, such as Rapid Estimate of Adult Literacy in Medicine (REALM)[ 39 ] or even some measure of formal education could be more informative. Nevertheless, the use of self-reported illiteracy in large epidemiological studies has been reported in the literature with consistent results [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 77%
“…The studies cut across some subject areas: quality of life and well-being of older people (e.g., Mwanyangala et al, 2010 ; Wilunda et al, 2015 ), sociodemographic inequalities in HIV testing and HIV prevalence in older people (e.g., Mtowa et al, 2017 ), living conditions and household arrangement (e.g., Chepngeno-Langat et al, 2019 ; Kyobutungi et al, 2010 ; Schatz et al, 2015 , 2018 ; Wilunda et al, 2015 ), and cardiovascular disease (CVD) management (e.g., Jardim et al, 2017 , 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…All biomarker measures were taken during the baseline in‐person interview via point‐of‐care blood testing, dried blood spot testing, and blood pressure testing, using previously described methodologies. 22 …”
Section: Methodsmentioning
confidence: 99%